Transformative agency of students as a resource to form civic consciousness in education system - M. V. Pevnaya; A. N. Tarasova; D. F. Telepaeva; D. S. Protasov (Образование и наука)
Introduction. The relevance of the study is associated with the need for the formation of civic consciousness among the young generation. It is important to create mechanisms for involving young people in active creative activity through volunteering and constructive political activity. In the current conditions, it is necessary to restructure the consciousness and correct the behaviour of young people by creating certain conditions for prosocial activity, mutual assistance and support for those who need it especially.Aim. The aim of the article is to assess the real practices and potential of civic participation of students in the Sverdlovsk region, identifying the sociocultural features of civic consciousness of high school students and students through the prism of their transformative agency and identifying the conditions of the educational environment for the expansion of youth prosocial activity in the interests of territorial development.Methodology and research methods. The methodological basis of the article is a set of theoretical ideas about the transforming agency of youth and the formation of socially responsible behaviour of young Russians as citizens of their country, region, and city of residence. The theory of civic consciousness has received a certain development in the article. The present article is based on the materials of the authors’ research project implemented in 2022 in the Sverdlovsk region. The authors analysed the data of a mass survey of young people in the Sverdlovsk region from 14 to 24 years old from 79 settlements of the region, carried out by the questionnaire method. 996 people were interviewed, the sample is representative, the error is no more than 3,5%. There are four quotas in its base: gender, age, main type of education (school, secondary school, university); type of city by population. The data of the quantitative survey are supplemented by the results of the analysis of social youth projects that received government support at the regional level in the subsidy competition of the Ministry of Education and Youth Policy of the Sverdlovsk Region in 2022–2023.Results and scientific novelty. The study demonstrated that the educational environment is designed and creates conditions for the acquisition of civic experience by young students today. On the one hand, projects, actions, information events should be called for the formation of civic consciousness in the development of transformative agency of youth. On the other hand, they should give young people the opportunity to realise and develop their transformative agency as citizens of their country, residents of their city through reflection, initiative, plans aimed at solving urgent social problems, and their implementation. Systematic work to create conditions for this in educational institutions should help complement the organisation of passive civic participation with mechanisms that help young Russians realise their active civic position, stimulate them to take real actions in the socio-political sphere. The study proves that civic experience and civic subjectivity, which manifests itself in various practices of civic participation, accumulates and is formed among young people depending on age. This is less expressed in high school students, and more expressed in university students. University students are more subjective; they do not just formally use resources for civic engagement, but try to accumulate civic knowledge with their help, consciously showing interest and intention in the sphere of such activity. The conditions of the environment of civic participation in the education system largely determine the differences in the subjective value characteristics of high school students and university students, revealing the transformative agency in the development of their civic consciousness.Practical significance. Considering the geopolitical challenges in Russian education today, the issue of implementing educational work with young people is acute. Given the special characteristics of the civic activity of Russian youth for the organisation of social work with high school students and university students, it is important to understand the potential of civic activity of the young generation, especially those characteristics possessed by the socially active part of schoolchildren and students for correcting the course of regional youth policy and improving the mechanisms of government support for youth projects in the education system.